2017
DOI: 10.1186/s12885-017-3901-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and efficacy of second-line targeted therapy in metastatic renal cell carcinoma: data from a national registry

Abstract: BackgroundIt is well known that patient characteristics and survival outcomes in randomized trials may not necessarily be similar to those in real-life clinical practice. The aim of the present study was to analyse second line treatment strategies in the real-world practice and to estimate the outcomes of patients treated with second-line targeted therapy for metastatic renal cell carcinoma (mRCC).MethodsThis is a retrospective, registry-based study using data from the national registry of targeted therapies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Five of these studies have been excluded from this review because of the update of the scope excluding sunitinib as it is not recommended at second line in the most up-to-date ESMO guidance for RCC 12. Five new studies, one RCT and four retrospective chart reviews were identified in the update and extension searches (including terms for lenvatinib with everolimus) run in January 2018, making a total of 12 included studies 13–15 19 20 27–33…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of these studies have been excluded from this review because of the update of the scope excluding sunitinib as it is not recommended at second line in the most up-to-date ESMO guidance for RCC 12. Five new studies, one RCT and four retrospective chart reviews were identified in the update and extension searches (including terms for lenvatinib with everolimus) run in January 2018, making a total of 12 included studies 13–15 19 20 27–33…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies (n=5144) met the inclusion criteria (table 1): five RCTs (one double-blind28 and four open-label13 15 20 28) and seven observational studies19 27 29–33 (retrospective cohort studies). Sample sizes varied from 101 (HOPE 205)15 to 821 (CheckMate 025)14 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations